2008
DOI: 10.1074/jbc.m710462200
|View full text |Cite
|
Sign up to set email alerts
|

Neuropoietin Attenuates Adipogenesis and Induces Insulin Resistance in Adipocytes

Abstract: Recent findings have implicated gp130 receptor ligands, particularly ciliary neurotrophic factor (CNTF), as potential antiobesity therapeutics. Neuropoietin (NP) is a recently discovered cytokine in the gp130 family that shares functional and structural features with CNTF and signals via the CNTF receptor tripartite complex comprised of CNTFR␣, LIF receptor, and gp130. NP plays a role in the development of the nervous system, but the effects of NP on adipocytes have not been previously examined. Because CNTF e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 52 publications
(62 reference statements)
0
30
0
Order By: Relevance
“…1), and activates tyrosine phosphorylation of gp130 followed by STAT3 phosphorylation and nuclear translocation in CNTFRexpressing neuroblastoma cells [4] and 3T3-L1 adipocytes [16]. Systemic injection of NP also stimulated STAT3 phosphorylation in white fat in vivo [16,17]. all these cytokines are secreted, with CLCF1 being secreted in complex with either cytokine receptor-like factor 1 (CRLF1) or soluble ciliary neurotrophic factor receptor (sCNTFR), and CRLF1 being secreted with p28.…”
Section: Specific Features Of Np Signallingmentioning
confidence: 97%
See 1 more Smart Citation
“…1), and activates tyrosine phosphorylation of gp130 followed by STAT3 phosphorylation and nuclear translocation in CNTFRexpressing neuroblastoma cells [4] and 3T3-L1 adipocytes [16]. Systemic injection of NP also stimulated STAT3 phosphorylation in white fat in vivo [16,17]. all these cytokines are secreted, with CLCF1 being secreted in complex with either cytokine receptor-like factor 1 (CRLF1) or soluble ciliary neurotrophic factor receptor (sCNTFR), and CRLF1 being secreted with p28.…”
Section: Specific Features Of Np Signallingmentioning
confidence: 97%
“…In cultured 3T3-L1 adipocytes, NP reduced expression of adipogenic genes when added while the cells were still preadipocytes [16]. Although NP uses the same receptor complex as CNTF, this effect was not observed with CNTF in 3T3-L1 cells [16,68] or by NP, CNTF or CLCF1 in more primitive bipotential mesenchymal cells [12]. Pretreatment of 3T3-L1 adipocytes and C57BL/6 mice with NP also attenuated the effects of insulin on Akt/STAT3 activation and insulin-stimulated glucose uptake [16].…”
Section: Biological Actions Of Npmentioning
confidence: 97%
“…2). Adipocytes are more than inert energy depots, and adipose tissue is a biologically active organ that carries out important (Green et al 1985;Kawai et al 2007) Antiadipogenic in primary rat preadipocytes (Wabitsch et al 1996b) and in human adipocytes (Wabitsch et al 1996a) Insulin/IGF-1 Proadipogenic Proadipogenic in 3T3-L1 cells (Green et al 1985;Smith et al 1988 Inhibitory Antiadipogenic in 3T3-L1 (Kawashima et al 1991), human marrow (Keller et al 1993), and human preadipocyte cells (Meng et al 2001) LTF Controversial No effect on 3T3-L1 adipogenesis (Hogan et al 2005;White et al 2008) Proadipogenic in 3T3-L1 cells (Aubert et al 1998) Antiadipogenic in bone marrow stromal cells (Gimble et al 1994) NP Inhibitory Antiadipogenic in 3T3-L1 cells (White et al 2008) OSM Inhibitory Antiadipogenic in 3T3-L1 cells (Miyaoka et al 2006;White et al 2008), mouse embryonic fibroblasts (Miyaoka et al 2006), and human adipose-derived mesenchymal cells (Song et al 2007) physiological processes including energy homeostasis and whole-body insulin sensitivity. Attenuating adipose tissue expansion can result in pathologies including insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous findings in the last decade have highlighted the differential effects of gp130 cytokines on important adipocyte functions. These studies have shown that adipocytes in vitro and adipose tissue in vivo are responsive to gp130 cytokines (Balhoff and Stephens 1998;Stephens et al 1998;Lagathu et al 2003;Rotter et al 2003;Zvonic et al 2003Zvonic et al , 2004Tenney et al 2005;White et al 2008) and exert differential effects on adipogenesis. To date, no gp130 cytokines have been shown to promote adipogenesis, but as shown in Table 1, several cytokines in this family have been shown to inhibit adipocyte development (Keller et al 1993;Meng et al 2001;Zvonic et al 2003Zvonic et al , 2004Sopasakis et al 2004;Hogan and Stephens 2005;Miyaoka et al 2006;Song et al 2007;White et al 2008).…”
Section: Glycoprotein 130 (Gp130) Cytokinesmentioning
confidence: 99%
“…The majority of studies support a role for OSM in promoting metabolic dysfunction. For example, it is well documented that OSM inhibits adipogenesis (23,24). In addition, OSM induces plasminogen activator inhibitor-1 (PAI-1) expression in murine adipocytes (22) and in human AT (25).…”
mentioning
confidence: 99%